Caffeine inhibits hepatitis C virus replication in vitro - Batista, Mariana N. [UNESP]; Carneiro, Bruno M. [UNESP]; Braga, Ana Cláudia S. [UNESP]; Rahal, Paula [UNESP] (Springer Nature, 2014)
Abstract Hepatitis C is considered the major cause of cirrhosis and hepatocellular carcinoma. Conventional treatment is not effective against some hepatitis C virus (HCV) genotypes; therefore, new treatments are needed. Coffee and, more recently, caffeine, have been found to have a beneficial effect in several disorders of the liver, including those manifesting abnormal liver biochemistry, cirrhosis and hepatocellular carcinoma. Caffeine acts directly by delaying fibrosis, thereby improving the function of liver cellular pathways and interfering with pathways used by the HCV replication cycle. In the current study, the direct relationship between caffeine and viral replication was evaluated. The Huh-7.5 cell line was used for transient infections with FL-J6/JFH-50 C19Rluc2AUbi and to establish a cell line stably expressing SGR-Feo JFH- 1. Caffeine efficiently inhibited HCV replication in a dosedependent manner at non-cytotoxic concentrations and demonstrated an IC50 value of 0.7263 mM after 48 h of incubation. These data demonstrate that caffeine may be an important new agent for anti-HCV therapies due to its efficient inhibition of HCV replication at non-toxic concentrations.